2019
DOI: 10.1016/j.tbs.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of changing travel patterns on travel satisfaction: A focus on recently relocated residents

Abstract: Previous studies indicate that travel satisfaction is affected by elements such as travel mode choice and trip duration. However, how people's satisfaction levels with travel adapt after changing their travel behaviour has not yet been analysed thoroughly. In this study we analyse travel satisfaction of 1,650 respondents who recently relocated to selected neighbourhoods in the city of Ghent (Belgium), and therefore changed their daily travel patterns (i.e., commute and leisure trips). Based on a two-step appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…6 In the past decade, many studies have investigated satisfaction with travel, often using the Satisfaction with Travel Scale (Ettema et al, 2011). Although this scale has proven to be a reliable measure of travel satisfaction (De Vos, Schwanen, Van Acker, & Witlox, 2015;Singleton, 2019a), some studies have instead used agreement ratings of statements, inspired by the Satisfaction with Life Scale (Diener, Emmons, Larsen, & Griffen, 1985), to measure satisfaction with daily travel (Bergstad et al, 2011), and satisfaction with commuting and leisure travel (De Vos, Ettema, & Witlox, 2019b). Studies indicate that people are in general relatively satisfied with their travel, especially with trips using active modes, having short durations, and for non-commute purposes (e.g.…”
Section: Examining Attitude Desire Intention Behaviour and Satisfaction In Travel Behaviour Researchmentioning
confidence: 99%
“…6 In the past decade, many studies have investigated satisfaction with travel, often using the Satisfaction with Travel Scale (Ettema et al, 2011). Although this scale has proven to be a reliable measure of travel satisfaction (De Vos, Schwanen, Van Acker, & Witlox, 2015;Singleton, 2019a), some studies have instead used agreement ratings of statements, inspired by the Satisfaction with Life Scale (Diener, Emmons, Larsen, & Griffen, 1985), to measure satisfaction with daily travel (Bergstad et al, 2011), and satisfaction with commuting and leisure travel (De Vos, Ettema, & Witlox, 2019b). Studies indicate that people are in general relatively satisfied with their travel, especially with trips using active modes, having short durations, and for non-commute purposes (e.g.…”
Section: Examining Attitude Desire Intention Behaviour and Satisfaction In Travel Behaviour Researchmentioning
confidence: 99%
“…A longitudinal evaluation of an e-cycling stimulation programme in the province of North-Brabant, the Netherlands, found that the commute satisfaction of car commuters increases over time after taking up e-cycling to work (De Kruijf, Ettema, & Dijst, 2019). Residential or job moves resulting in shorter commute distances and more active travel have been found to result in higher levels of commute satisfaction (De Vos, Ettema, &Witlox, 2019, for movers to Ghent, Belgium, andSchneider &Willman, 2019, for employees at the University of Wisconsin-Milwaukee). This shows that changes to commuting can influence commute satisfaction.…”
Section: Satisfaction With the Commutementioning
confidence: 99%
“…Studies on mode shift have been largely motivated by a need to understand potential changes in response to proposed large infrastructure projects or substantially new services such as rapid transit or metro rail systems (11) and policy interventions such as congestion pricing (12) and fare subsidy. Most of the data on such mode shift studies are elicited using stated preference (SP) surveys because they are intended to examine potential mode responses to a new environment.…”
Section: Mode Shift and The Type Of Modes Shiftedmentioning
confidence: 99%